2018
DOI: 10.5539/ijbm.v13n6p84
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Content: A Management Framework

Abstract: This paper aims to introduce a model for social media content management that is focused on both the strategic and operational levels to guide companies in setting, formulating and spreading social media marketing content and monitoring the achieved results. The framework has been realized considering different cognitive goals related to the organizational unit responsible of the development of the content marketing processes, corporate content identity, decision making elements for digital content creation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The development of information technology has significantly changed the functioning of contemporary organizations in different areas (Ngai et al., 2015). This applies not only to such spheres of the organization's activities as marketing (Agresta and Bonin, 2010; Berthon et al., 2012), advertising (Okazaki and Taylor, 2013), logistics (Pierce, 2013), sales or banking (Bonsóna et al., 2012; Bonsóna and Flores, 2012) but also in the scope of work organization (Confetto and Siano, 2018; Dreher, 2014) or project management (Delerue and Sicotte, 2017; Harrin, 2012). Thanks to mobile technology and social media (SM), the way of communication between members of project teams and the style of managing them have changed.…”
Section: Introductionmentioning
confidence: 99%
“…The development of information technology has significantly changed the functioning of contemporary organizations in different areas (Ngai et al., 2015). This applies not only to such spheres of the organization's activities as marketing (Agresta and Bonin, 2010; Berthon et al., 2012), advertising (Okazaki and Taylor, 2013), logistics (Pierce, 2013), sales or banking (Bonsóna et al., 2012; Bonsóna and Flores, 2012) but also in the scope of work organization (Confetto and Siano, 2018; Dreher, 2014) or project management (Delerue and Sicotte, 2017; Harrin, 2012). Thanks to mobile technology and social media (SM), the way of communication between members of project teams and the style of managing them have changed.…”
Section: Introductionmentioning
confidence: 99%
“…If positively addressed, the viral diffusion of user-generated brand content can increase brand awareness, generate new contacts, stimulate engagement on social networks and ultimately strengthen brand trust and loyalty (Arnhold, 2010;Ashley and Tuten, 2015). Usergenerated branded content should be considered from a cocreative perspective already during the planning of social media content (Confetto and Siano, 2018) and, accordingly, brand hijacking activities can also be regarded as an enrichment and growth opportunity for the brand. Wipperfürth (2005) stressed the possibility of transforming fortuitous brand hijacking into a co-creative activity if the company adopts a strategy aimed at transforming the non-collaborative activity into a collaborative one (collaborative co-creation actions).…”
Section: Implications For Practicementioning
confidence: 99%
“…More studies are needed to examine the activities, techniques and tools used to monitor and manage brand hijacking, especially in terms of reputational damage and brand re-positioning. Exploring different methods for the real-time monitoring of social media and anti-brand communities could help in revealing and anticipating both antibrand sentiments and constructive feedback, which could also help in addressing social media content and brand management decisions (Anker et al, 2015;Confetto, 2015;Klostermann et al, 2018). Monitoring techniques could be developed to support the identification, for example, of doppelganger brand image (Thompson et al, 2006) and related cultural aspects disseminated by potential brand avoiders.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…It is because without proper understanding about the factors for managing social content, organizations would face a certain amount of difficulty to generate accurate results based on input from social content. However, the literature has shown that there is a lack of academic research concerning the area of social content management [5], [6]. Research done by [7] revealed that the conceptual aspects of social content management were given less attention as compared to the technological aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Further reviews of the literature showed that the focus of existing frameworks on social content management models or frameworks fail to consider the main attribute of social media interactions, that of value-co-creation. These existing models and frameworks focused more on the value of the social content to organizations [5], [6], [8], and chose not to emphasize on the co-created value [9]. The existing framework also places less emphasis on the production of service innovations based on managed social content [8], [10].…”
Section: Introductionmentioning
confidence: 99%